Posterior fixation suture and convergence excess esotropia - Steffen, Heimo; Auffarth, Gerd U.; Kolling, Gerold (Strabismus, 1998)
The present study investigates the results of Cüppers' `Fadenoperation' in patients with non-accommodative convergence excess esotropia. Particular attention is given to postoperative eye alignment at distance fixation. Group 1 (n=96) included patients with a `normal' convergence excess. The manifest near angles (mean ET 16.73° ± 6.33°, range 4°-33°) were roughly twice the size of the distance angles (mean ET 6.50° ± 3.62°, range 0°-14°). These patients were treated with a bilateral fadenoperation of the medial recti without additional eye muscle surgery. Three months after surgery, the mean postoperative angles were XT 0.5° ± 3.3° (range XT 11°-ET 5°) for distance fixation, and ET 2.7° ± 3.6° (range XT 5°-ET 14°) for near fixation, respectively. Postoperative convergent angles at near fixation >ET 10° were present in two patients (1.9%). Group 2 (n=21) included patients with a mean preoperative distance angle of ET 9.2° ± 3.7° (range 6°-16 °) and a mean preoperative near angle of ET 23.4° ± 3.1° (range 16°-31°). These patients were operated on with a bilateral fadenoperation of the medial recti and a simultaneous recession of one or both medial rectus muscles. Mean postoperative angles were XT 0.5° ± 4.6° (range XT 12°-ET 7°) for distance fixation and ET 1.4° ± 4.5° (range XT 8°-ET 13°) for near fixation, respectively. In this group, 2 patients (10.6%) had a postoperative exotropia >XT 5° at distance fixation, and two patients had residual esotropia >ET 10° at near fixation. Group 3 (n=17) included patients with a pronounced non-accommodative convergence excess. Near angle values (mean of 17.8° ± 5.3°, range ET 7°-26°) were several times higher than the distance angle values (mean ET 1.9° ± 4.2°, range XT 3° -ET 6°). These patients were treated with a bilateral fadenoperation of the medial recti and a simultaneous resection of one or both medial rectus muscles. Mean postoperative angles were ET 0.2° ± 4.7° (range XT 8°-ET 6°) for distance fixation and 5.3° ± 6.1° (range XT 3°-ET 12°) for near fixation, respectively. One patient had a postoperative distance angle >XT 5°, whereas two patients displayed postoperative convergent angles >ET 5° at near fixation.
Elektronische Reproduktion der Druck-Ausgabe 8. Juli 2009
Gesehen am 09.11.2023